PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MELALUI PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK - Rifqah Husnul Khatimah (Departemen Matematika, 2018)
Mathematical problem solving ability is one of abilities that is expected to be develop optimally for learners. However, mathematical problem solving ability of students in eighth grade at SMPN 4 Padang is still low. One of the learning approach that can solve this problem is Realistic Mathematics Education approach.The aims of this research isto know whether mathematical problem solving ability of students who study by Realistic Mathematics Education approach is better than conventional learning in eighth grade at SMPN 4 Padang. The kind of this research was quasi eksperiment with static grup design. The samples of this research was the students at class VIII.4 and class VIII.3. The result of the research show that mathematical problem solving ability of students who study by Realistic Mathematics Education approach is better than conventional learning. Keywords—conventional learning,mathematical problem solving ability of students, Realistic Mathematics Education approach.